2018
DOI: 10.1111/bcp.13531
|View full text |Cite
|
Sign up to set email alerts
|

Balancing early access with uncertainties in evidence for drugs authorized by prospective case series – systematic review of reimbursement decisions

Abstract: AimsTo review clinical and cost‐effectiveness evidence underlying reimbursement decisions relating to drugs whose authorization mainly is based on evidence from prospective case series.MethodsA systematic review of all new drugs evaluated in 2011–2016 within a health care profession‐driven resource prioritization process, with a market approval based on prospective case series, and a reimbursement decision by the Swedish Dental and Pharmaceutical Benefits Agency (TLV). Public assessment reports from the Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“… 3 These may cause a medium level of composite uncertainty to be weighed differently and considered acceptable, whereas a high level of uncertainty is not. The importance of unmet medical need in HTA decision making has been highlighted by others that studied uncertainty associated with medicines that had been approved based on data from uncontrolled trials 11 , 24 or through early access pathways. 12 Both uncontrolled trials and approval through early access pathways are typical characteristics of medicines that address an unmet medical need, 25 , 26 , 27 and may also have played a role in our study.…”
Section: Discussionmentioning
confidence: 99%
“… 3 These may cause a medium level of composite uncertainty to be weighed differently and considered acceptable, whereas a high level of uncertainty is not. The importance of unmet medical need in HTA decision making has been highlighted by others that studied uncertainty associated with medicines that had been approved based on data from uncontrolled trials 11 , 24 or through early access pathways. 12 Both uncontrolled trials and approval through early access pathways are typical characteristics of medicines that address an unmet medical need, 25 , 26 , 27 and may also have played a role in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this may call for a more solid evidence base. Conversely, new cancer drugs are sometimes approved based on limited evidence regarding patient-relevant effects [ 52 ], and not all meet the threshold for a clinically meaningful effect [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was found that expedited drugs were based on early studies which relied on surrogate outcomes [ 107 , 108 ], which do not necessarily translate to long-term clinical benefits [109] . Irrespective of this, analyses to data has indicated that both NICE and SMC are willing to grant positive recommendations to novel medicines based on uncertain evidence such as prospective case studies [110] . Therefore, it is important that any move towards accelerated access to medicines is combined with thorough monitoring of real-world efficacy, and if necessary renegotiation of prices.…”
Section: Changes To Pharmaceutical Licensing and The Use Of Real-worl...mentioning
confidence: 99%